MCM3AP-AS1: An Indispensable Cancer-Related LncRNA - Yu, Xiao; Zheng, Qingyuan; Zhang, Qiyao; Zhang, Shuijun; He, Yuting; Guo, Wenzhi (Frontiers in Cell and Developmental Biology, 2021)
Long non-coding RNAs (lncRNAs) are a class of RNA molecules with transcripts longer than 200 nucleotides that have no protein-coding ability. MCM3AP-AS1, a novel lncRNA, is aberrantly expressed in human cancers. It is significantly associated with many clinical characteristics, such as tumor size, tumor-node-metastasis (TNM) stage, and pathological grade. Additionally, it considerably promotes or suppresses tumor progression by controlling the biological functions of cells. MCM3AP-AS1 is a promising biomarker for cancer diagnosis, prognosis evaluation, and treatment. In this review, we briefly summarized the published studies on the expression, biological function, and regulatory mechanisms of MCM3AP-AS1. We also discussed the clinical applications of MCM3AP-AS1 as a biomarker.